PARENTERAL NUTRITION – ASPECTS OF SPECIFIC POPULATIONS - Mirković, Dušica (Archives of Pharmacy, 2023)
Parenteral nutrition (PN) provides nutrients and water to patients who are not able or allowed to feed by enteral route. In addition, the composition of PN mixture should be adjusted to comply with individual patient’s needs, depending on age and disease state. Consequently, different associations for parenteral and enteral nutrition have issued guidelines for the preparation and administration of PN mixtures in different population groups (1). The importance of PN has increased over the years, which is visible from the global PN market report (2). Namely, growing geriatric and prenatal populations, increasing prevalence of chronic diseases and demand for home patients care have resulted in increased utilization of PN formulations. in the meanwhile, new technological developments and findings from clinical studies facilitate formulation, preparation and administration of PN products. Also, growing demands from regulatory and professional authorities require the implementation of contemporary pharmaceutical-technical procedures in the development of PN preparations. The major challenges in this area include the choice of ingredients, manufacturing/preparation methods, administration route and dosing regime, as well as decision making on the need for PN in specific patients. Certain factors restrict wider application of PN products, such as the limited number of commercially available mixtures, high manufacturing/preparation costs, shortage of skilled staff, risks of complications and issues related to PN adjustments to meet individual patient’s needs. Such conditions imply the need for additional research to increase efficacy and safety of PN therapy, and allow wider accessibility of PN products to specific patient groups.